Social networking sites: a novel portal for communication. Issue 1007 (4th September 2009) - Farmer, A D; Bruckner Holt, C E M; Cook, M J; Hearing, S D
Abstract : Background: The internet has transformed many spheres of society. Most notably the advent of social networking websites, such as MySpace, Bebo and Facebook, have attracted many millions of users worldwide. There are over 350 such sites in operation across the internet. There is a paucity of data in the adult literature examining the medical usage of this interesting facet of modern life. Aims: To ascertain whether Facebook has user groups that are connected with common medical conditions, and to classify the user groups that were identified as well as enumerating the number of individual users contained therein. Methods: We conducted a search of the entire Facebook website between December 2007 and January 2009. We used medical and lay nomenclature for the most prevalent non-communicable diseases as identified from the World Health Organisation Burden of Disease publication to identify whether they were represented among individual Facebook users and user groups. Results: We identified 290 962 individual users who were part of 757 groups. Patient groups accounted for 47.4%, patient/carer support groups 28.1%, fund raising groups 18.6%, and others 5.8%. Notably, there were other groups containing representations from the scientific research community in addition to educational resources. The groups with the most individual members pertained to malignant neoplasms and cardiovascular disease (141 458 users) consistent with their worldwide prevalence. Conclusions: Facebook is providing a readily accessible portal for patients, carers and healthcare professionals to share their experiences of investigation, diagnosis and management of disease. Furthermore, this technology is being used for research, education and fundraising. Further research is warranted to explore the further potential of this new technology.